Prompt photons in photoproduction at HERA - Aaron, Francisc Dionisie; Schöning, André; Schultz-Coulon, Hans-Christian (The European physical journal. C, Particles and fields, 2010)
The production of prompt photons is measured in the photoproduction regime of electron–proton scattering at HERA. The analysis is based on a data sample corresponding to a total integrated luminosity of 340 pb−1 collected by the H1 experiment. Cross sections are measured for photons with transverse momentum and pseudorapidity in the range 6<\ensuremathEγT<15  GeV and −1.0<η γ<2.4, respectively. Cross sections for events with an additional jet are measured as a function of the transverse energy and pseudorapidity of the jet, and as a function of the fractional momenta x γ and x p carried by the partons entering the hard scattering process. The correlation between the photon and the jet is also studied. The results are compared with QCD predictions based on the collinear and on the k T factorization approaches.